AB0481 Vitamin D Levels in Children, Adolescents, and Young Adults with Juvenile Onset Systemic Lupus Erythematosus: A Transversal Study. (10th June 2014) - Stagi, S.; Cavalli, L.; Bertini, F.; Lepri, G.; Matucci Cerinic, M.; Brandi, M.L.; Falcini, F.
Abstract : Background: The interest in the association between 25(OH) D and Systemic Lupus Erythematosus (SLE) started in the last decade when VIT D status was related to low bone mass in these patients. Several studies have shown that the majority of SLE patients have 25(OH) D deficiency, highlighting the possible association between SLE and 25(OH) D. While VIT D deficit in SLE may be related to lack of sun exposure, several studies report a positive association between SLE activity and 25(OH) D deficiency.VIT D seems to be important in decreasing the risk of cancer, autoimmune, infectious and cardiovascular diseases. This effect may be related to VIT D regulation of immune function. In vitro studies have detected that vitamin D metabolites up-regulate the anti-inflammatory and down-regulate pro-inflammatory cytokines, and enhance the T-reg production. While numerous studies have been performed in adulthood SLE, a few data are available in juvenile onset SLE (JSLE), despite reduced bone mass and increased fracture risk are well recognized as one of the major health problems in these patients. Therefore, VIT D status should have a role in reducing bone mass in JSLE Objectives: The purpose of this study was: 1. To assess serum 25(OH) D levels in children, adolescents, and young adults with JSLE; 2. To identify the risk factors for vitamin D deficiency in this population Methods: Fifty-five consecutive patients with JSLE (37 F, 9 M, mean age 18.9±6.3 yrs) entered the study. In all DXA scans at the lumbar spine, serum calcium and phosphate, bone alkaline phosphatase (BSAP), parathyroid hormone (PTH), and 25-hydroxyvitamin D (25(OH) D) were assessed the same day Results: JSLE patients showed significantly reduced 25(OH) D levels than controls (p<0.005), in particular the values were lower in those with active disease in comparison to patients with inactive disease (p<0.05). JSLE patients showed significantly reduced total calcium levels (p<0.001), and higher phosphate levels (p<0.001), BSAP (p<0.001), and PTH (p<0.001) than controls. Besides, JSLE patients had a reduced spine BMAD SDS in comparison to controls (p<0.001), with significant higher values in those with 25(OH )D sufficiency and insufficiency, respect to patients with 25(OH) D deficiency (p<0.001) Conclusions: JSLE patients have a significant lower 25(OH) D levels than controls, and subjects with active disease have significant reduced 25(OH) D levels in comparison to those with inactive disease, and have a higher risk of developing 25(OH) D deficiency. Our results seem support a role of 25 (OH) D deficiency in the bone growth of JSLE patients. So, vitamin D might be an additional factor to improve the normalization of bone mass and quality in subjects with JSLE References: Attar SM, Siddiqui AM. Vitamin d deficiency in patients with systemic lupus erythematosus. Oman Med J. 2013, 28:42-7. Adorini L, Penna G. Control of autoimmune diseases by the vitamin D endocrine system. Nat Clin Pract Rheumatol. 2008, 4:404-12 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3645